Analysis of International Human Rights Court Rulings Against Member States: A Review of Compliance and Its Consequences - Ni Nyoman Putri Purnama Santhi; I Putu Harry Suandana Putra; I Nengah Nuarta (Jurnal Indonesia Sosial Sains, 2024)
The international human rights framework requires cooperation and compliance from member states. Despite various mechanisms offering human rights protection, challenges persist in ensuring compliance and responding to human rights violations worldwide. In this research phase, a systematic literature review was conducted, employing an approach that referenced various sources available in various research databases. The research findings indicate that in analyzing the compliance of member states with international human rights court decisions, it can be concluded that the implementation of decisions involves a complex process and entails various factors. The mechanisms for implementing decisions at the national level require the involvement of legal institutions, civil society participation, collaboration with relevant parties, and education for law enforcement agencies